Confocal Laser Endomicroscopy and Molecular Imaging in Barrett Esophagus and Stomach - Choi, Kwi-Sook (The Korean Society of Gastrointestinal Endoscopy, 2014)
Detection of premalignant lesions in the upper gastrointestinal tract may facilitate endoscopic treatment and improve survival. Despite technological advances in white light endoscopy, its ability to detect premalignant lesions remains limited. Early detection could be improved by using advanced endoscopic imaging techniques, such as magnification endoscopy, narrow band imaging, i-scanning, flexible spectral imaging color enhancement, autofluorescence imaging, and confocal laser endomicroscopy (CLE), as these techniques may increase the rate of detection of mucosal abnormalities and allow optical diagnosis. The present review focuses on advanced endoscopic imaging techniques based on the use of CLE for diagnosing premalignant lesions in Barrett esophagus and stomach.